Wybrane problemy diagnozy opisowej w socjoterapii – aspekty teoretyczne oraz związki z funkcjonowaniem zawodowym socjoterapeutów - Jankowiak, Barbara; Soroko, Emilia (Wydawnictwo Naukowe UAM, 2014)
The matter of psychological diagnosis in socio-therapy is a relatively new area of theoretical reflection and empirical research. The piece of research presented here deals with socio-therapists’ perspective and regards developing the picture of the psychological problems of groups participants and the consequences of the described manner of perceiving problems in socio-therapists’ professional functioning. It was explored what kind of descriptive diagnosis is made by socio-therapists and certain general tendencies in identifying the relational problems were observed (e.g. more frequent observing the problems with adults or the child with itself), as well as the participants and their families (mainly the problems with learning, ADHD at children and violence and alcoholism in families). The co-occurrence of the individual’s and family’s problems identified here corresponds to other clinical psychology studies of children and teenagers (especially co-occurence of fear disorders, ADHD of the disorders of learning in the alcoholic family environment). The relations between the tendencies to recognize particular problems and the subgroups of these problems (relational and nozological aspects) and professional functioning of the socio-therapists were described. It has been noticed that the severity of diagnoses is related to a greater amount of negative feelings in professional works and there are no significant relations between identifying the problems and a hope for a professional success. The results have been discussed in the context of the light on socio-therapy as psycho-pedagogical help.
Selected Issues Concerning Descriptive Diagnosis in Socio-Therapy – Theoretical Aspects and Links with Socio-therapists’ Professional Functioning
Keywords: socio-therapy; socio-therapists; problems of socio-therapy participants; diagnosis in socio-therapy